Analysis of ALK, MYCN, and the ALK ligand ALKAL2 (FAM150B/AUGα) in neuroblastoma patient samples with chromosome arm 2p rearrangements. Issue 1 (2nd September 2019) - Javanmardi, Niloufar; Fransson, Susanne; Djos, Anna; Umapathy, Ganesh; Östensson, Malin; Milosevic, Jelena; Borenäs, Marcus; Hallberg, Bengt; Kogner, Per; Martinsson, Tommy; Palmer, Ruth H.
Abstract: Gain of chromosome arm 2p is a previously described entity in neuroblastoma (NB). This genomic address is home to two important oncogenes in NB— MYCN and anaplastic lymphoma kinase ( ALK ). MYCN amplification is a critical prognostic factor coupled with poor prognosis in NB. Mutation of the ALK receptor tyrosine kinase has been described in both somatic and familial NB. Here, ALK activation occurs in the context of the full‐length receptor, exemplified by activating point mutations in NB. ALK overexpression and activation, in the absence of genetic mutation has also been described in NB. In addition, the recently identified ALK ligand ALKAL2 (previously described as FAM150B and AUGα) is also found on the distal portion of 2p, at 2p25. Here we analyze 356 NB tumor samples and discuss observations indicating that gain of 2p has implications for the development of NB. Finally, we put forward the hypothesis that the effect of 2p gain may result from a combination of MYCN, ALK, and the ALK ligand ALKAL2 .